Clinical and ultrasonographic features of 104 knee joints in hemodialysis patients: impact of age, gender, and hemodialysis duration: a descriptive cross-sectional study - Samar Tharwat; Marwa Saleh; Rabab Elrefaey; Mona Kamal Nassar; Mohammed Kamal Nassar (BMC Musculoskeletal Disorders)
Abstract Background and objectives Hemodialysis (HD) patients struggle with musculoskeletal disorders. This study aimed to examine knee clinical and musculoskeletal ultrasonographic (MSUS) characteristics in HD patients and to evaluate the influence of age, gender, and HD duration. Materials and methods This cross-sectional descriptive study included 52 patients (104 knee joints) on regular HD for at least 6 months. Demographic, clinical, therapeutic, and laboratory data were collected. Chronic knee pain was assessed for duration, intensity, and laterality. Swelling, crepitus, and tenderness were assessed in both knees. EULAR-standardized knee MSUS evaluations were performed on all patients. The patients were then compared based on age, gender, and HD duration. Results The mean age of the patients was 52.4 ± 14.15 years, with 25 females and 27 males, median duration of HD was 3.5 years. Chronic knee pain was present in 31 of 104 knees (29.8%). The scanned 104 knee joints had at least one MSUS finding in 91 (87.5%): suprapatellar effusion in 57 (54.8%), synovial thickening in 13 (12.5%), abnormal cartilage morphology in 68 (65.4%), quadriceps tendon abnormalities in 58 (55.8%), patellar tendon abnormalities in 34 (32.7), medial meniscus abnormalities in 30 (28.8%), lateral meniscus abnormalities in 13 (12.5%), and Baker cyst in 5 (4.8%). MSUS abnormalities were significantly more prevalent in HD patients older than 40 years (94.9% vs. 65.4; p < 0.001). Chronic Knee Pain was more prevalent in females than males (40% versus 20%, respectively). Regarding HD duration, quadriceps, and patellar tendons exhibited more MSUS abnormalities in patients with HD duration > 3 years (86.5% vs. 42.0% and 38.9% vs. 25%, respectively) compared to others. Conclusion MSUS findings of the knee are prevalent among HD patients, particularly those of female gender, older age, and longer duration of HD. These findings could be subclinical. Typically, the severity of suprapatellar effusion is related to additional structural abnormalities.